The role of the gut microbiota in inflammatory bowel diseases - Martinov Nestorov, Jelena; Sokić Milutinović, Aleksandra (Medicinski podmladak, 2025)
The gut microbiota plays a pivotal role in maintaining gastrointestinal homeostasis and regulating immune responses. Inflammatory bowel diseases (IBD), Crohn’s disease and ulcerative colitis, are associated with significant alterations in the composition and function of the intestinal microbiota—referred to as dysbiosis. Dysbiosis may contribute to impaired mucosal barrier function, heightened inflammation, and abnormal immune responses. The mechanisms by which microbiota influences the course of IBD include altered production of short-chain fatty acids, reduced microbial diversity, and an imbalance between protective and pathogenic bacteria. Interactions between the microbiota and immune cells, and their roles in initiating and sustaining inflammation, are subjects of ongoing research. Therapeutic strategies aiming to modulate gut microbiota, such as probiotics, prebiotics, dietary interventions, and fecal microbiota transplantation (FMT), show promise in alleviating symptoms and prolonging remission in IBD patients. A deeper understanding of the complex role of the microbiota paves the way for personalized medicine and novel therapeutic approaches in the management of inflammatory bowel diseases.